(untitled) (Annals of Medical Research, 2022)
Aim: This study aimed to compare the cognitive functions of individuals with spinal cord injury (SCI) and age- and education level-matched healthy controls, and to compare the cognitive functions between individuals with T6 or rostral and T6 caudal injuries. Materials and Methods: This prospective and cross sectional study included 50 individuals with SCI and 47 age- and education level-matched healthy controls. The SCI individuals were divided into two groups as those with T6 or rostral (n = 20) and T6 caudal (n = 30) injuries. All participants underwent the Addenbrook Cognitive Examination-Revised (ACE-R) test to assess memory, attention and orientation, language, and verbal fluency. Results: The memory, verbal fluency, and language subgroups of the ACE-R were significantly higher in the control group than in the SCI group. Compared with the control group, memory, verbal fluency, and language subscores were significantly reduced in individuals with T6 or rostral injury, and memory and verbal fluency were in individuals with T6 caudal injury. However, there was no significant difference in any of the ACE-R subscores between individuals with T6 or rostral and T6 caudal injuries. Conclusion: Significant differences in certain parts of cognitive functioning were found in individuals with SCI compared with age- and education level-matched controls. However, no significant differences were noted in any parts of cognitive functioning between individuals with T6 or rostral and T6 caudal injuries. Although cognitive impairment is an important sequelae following SCI, autonomic dysfunctions appear to have no effect on cognitive impairments in this population.